Quality in Museums as a Way to Increase Sustainability - Pop, Izabela Luiza; Borza, Anca (European Journal of Sustainable Development, 2016)
Due to the high accent put on sustainable development of communities and on the role played by cultural organisations in this development process, this research starts from the hypothesis that quality may represent a path through which museums can achieve a higher level of sustainability. This hypothesis was tested through semi-structured interviews with experts from museums. The qualitative research showed that museums sustainability has to be measured through quantitative indicators but also through some quality-related indicators. Despite the fact that all experts pointed out a connection between sustainability measurement and quality, they argued that very few Romanian museums are carrying out such studies. Often, museums see quality measurement as something expensive, and thus unaffordable. Based on these facts, the second part of the paper seeks to highlight that quality is a much simpler tool than it is considered and museums can use this tool for improving their sustainability. Thus, the concept of museum quality is clarified by presenting the factors influencing it and some practical models which can be used by museums for measuring quality. By combining empirical and theoretical research, this paper may be of interest for other scholars studying museums sustainability and quality, but also for people working in museums. Keywords: museum quality; sustainability; development; improvement; SERVQUAL; HISTOQUAL JEL classification: M10; Q01;